Optimal power distributed control of the DC microgrid in meshed configuration - Yang, Zhichun; Yang, Fan; Chen, Jiawen (Frontiers in Energy Research, 2023)
This paper proposes a Lyapunov-based power sharing control scheme and a fixed-time-based distributed optimization algorithm to achieve optimal power sharing of sources in a DC microgrid. The Lyapunov-based controller is designed based on so-called ratio consensus protocol, where it drives the sources to a desired proportional power sharing by regulating the voltage profile of the DC microgrid. The distributed optimization optimizer is established by integrating a finite-time weighted consensus algorithm with an iterative algebraic operation, where it calculates the optimal power dispatch on the target of minimizing the generation cost. The optimizer receives the current output power of the controlled DC microgrid and sends the obtained power dispatch to the power sharing controller as the proportionality coefficients. Both the controller and optimizer are carried out in a fully distributed way. Under the framework of the Lyapunov method, stability analysis of the DC microgrid with the proposed control scheme, as well as convergence and optimality analysis of the distributed optimization algorithm, is provided. However, the influence of the time delay of the controller on the system remains to be further investigated in future work.